2018
DOI: 10.1016/j.neuropsychologia.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive resource and foreknowledge dependence of auditory perceptual inference

Abstract: Auditory perceptual inference engages learning of complex statistical information about the environment. Inferences assist us to simplify perception highlighting what can be predicted on the basis of prior learning (through the formation of internal "prediction" models) and what might be new, potentially necessitating an investment of resources to remodel predictions. In the present study, we tested the hypothesis that sound sequences with multiple levels of predictability may rely on cognitive resources and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…Thus, our previous notion of the nature of the first impression bias is expanded by the current results. Whereas the previous two-tone sequence studies Frost et al, 2018Frost et al, , 2016Mullens et al, 2016;Todd et al, 2011Todd et al, , 2013 showed an effect of the initial stimulus probability on processing the same sounds later in the sequence even after their probabilities have changed, the results obtained from the current three-tone sequences suggest that also the initial variability of the sound features can impact on how the same sounds are processed later in the sequence, even after their probabilities have varied. This means that primacy bias effects rely on a representation encoding more than just the initial probabilities; this representation also includes some estimate of featural variabilities.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Thus, our previous notion of the nature of the first impression bias is expanded by the current results. Whereas the previous two-tone sequence studies Frost et al, 2018Frost et al, , 2016Mullens et al, 2016;Todd et al, 2011Todd et al, , 2013 showed an effect of the initial stimulus probability on processing the same sounds later in the sequence even after their probabilities have changed, the results obtained from the current three-tone sequences suggest that also the initial variability of the sound features can impact on how the same sounds are processed later in the sequence, even after their probabilities have varied. This means that primacy bias effects rely on a representation encoding more than just the initial probabilities; this representation also includes some estimate of featural variabilities.…”
Section: Discussioncontrasting
confidence: 86%
“…Remarkably, this limitation disappears if the changeover between languages is cued by a period of silence and if participants receive explicit instruction on the existence of a second structure. This is precisely what happened in Frost et al () when participants heard the sequence depicted in Figure a and were told beforehand about the sequence structure. Although participants were asked to watch a movie and ignore the sounds just as in the version of the task with no explicit knowledge of the sequence, but in this case, the MMN elicited by deviants was large across the entire period of both block types, therefore, not showing the pattern of lower precision for the alternate block.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In previous studies, differential modulations of MMN amplitude to the first and second deviant tone have persisted across as many as four repetitions of the same sound sequences (36), and are shown only to be altered when superordinate patterning is abolished or violated (35, 65) or if the participant has prior experience with the sounds (48) or prior knowledge of the sequence structure (66). The apparent failure to override a first-impression, even after four repetitions of the same sound sequence, implies that the system maintains differential precision weightings for the two deviants unless a substantive level of surprise is encountered (36).…”
Section: Discussionmentioning
confidence: 96%